Perancangan Mesin Penggulung Dinamo Semi-Otomatis - Yusup Nur Rohmat; Rachmatullah; Rizky Maulana Akbar; Badruzzaman; Leo Van Gunawan; Octavianus Ardhian Nugroho (Politeknik Negeri Indramayu, 2022)
Home industry for dynamo repair in Sindang Village, Sindang District, Indramayu Regency, in carrying out its business to repair electric motors, dynamos, and distribution transformers, is done manually using a mechanical counter. The damage that often occurs in this equipment occurs in the coil, usually caused by being overloaded so that it burns. Winding the coils/coils on the dynamo can be done manually or using a winding machine. The type of winding machine commonly used by the dynamo home industry in Sindang Village, Sindang District, Indramayu Regency, still uses a mechanical counter. The accuracy of the number of windings affects the result of the quality of the repairs, apart from the type of winding wire applied. The research method used is quantitative experimental research. So that the result is that the automation process of the dynamo roller machine has been successfully implemented; reading the results using a limit switch still needs to be applied at high rotation (above 1 rpm). This can be corrected by using another sensor (Photoelectric Optocoupler). In the calculation planning results from the semi-automatic dynamo winding machine, the moment of inertia is 49,092.6mm2, displacement is 200.1, loading is 4,924.8 kg.mm, and the most considerable stress is 10,050 N/m2. In contrast, the slightest stress is 0,087 N/m2.